2008
DOI: 10.1016/j.anaerobe.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Human-derived probiotic Lactobacillus reuteri demonstrate antimicrobial activities targeting diverse enteric bacterial pathogens

Abstract: Lactobacillus reuteri is a commensal-derived anaerobic probiotic that resides in the human gastrointestinal tract. L. reuteri converts glycerol into a potent broad-spectrum antimicrobial compound, reuterin, which inhibits the growth of gram-positive and gram-negative bacteria. In this study, we compared four human-derived L. reuteri isolates (ATCC 55730, ATCC PTA 6475, ATCC PTA 4659 and ATCC PTA 5289) in their ability to produce reuterin and to inhibit the growth of different enteric pathogens in vitro. Reuter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
196
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(214 citation statements)
references
References 32 publications
5
196
0
8
Order By: Relevance
“…Third, probiotics could secrete antibacterial substances. It has been suggested that the antibacterial activity of the L. reuteri is related to an antimicrobial substance called reuterin which has bactericidal and bacteriostatic activities against a number of gram positive and negative bacteria and even some fungi [Hamilton-Miller, 2003;Spinler et al 2008]. Fourth, some strains of probiotics are known to have anti-inflammatory activity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Third, probiotics could secrete antibacterial substances. It has been suggested that the antibacterial activity of the L. reuteri is related to an antimicrobial substance called reuterin which has bactericidal and bacteriostatic activities against a number of gram positive and negative bacteria and even some fungi [Hamilton-Miller, 2003;Spinler et al 2008]. Fourth, some strains of probiotics are known to have anti-inflammatory activity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These findings further support adhesion mechanisms in the probiotichost interaction. In addition, L. reuteri strains inhibit enteropathogenic E. coli by direct antimicrobial activity attributable to secreted reuterin (54) or to the repression of genes expressed by pathogenic E. coli (21).…”
Section: Cd62lmentioning
confidence: 99%
“…The mechanisms that underlie this protection have not been clearly identified, but might include an increase in competitive exclusion. Various L. reuteri strains produce an array of antimicrobial compounds that inhibit pathogens in vitro (76,77). The best characterized of those, reuterin, is a mixture of different forms of beta-hydroxypropionaldehyde (3-HPA) that have bactericidal and bacteriostatic activity against a wide range of bacterial pathogens (77).…”
Section: Making An Impact: Beneficial Effects Conferred By L Reuterimentioning
confidence: 99%